Shariah Audit Practices In Malaysian Islamic Banks: An Audit Expectation Gap Analysis - Supiah Salleh (Universiti Sains Islam Malaysia, 2024)
Compliance is one of major concerns of practitioners, scholars and stakeholders in Islamic financial industry. In addressing the concern, Shariah audit practice in IFIs could play the important mechanism in ensuring Shariah compliance. Shariah audit strengthens the Shariah compliance and enhances the integrity of Islamic Financial Institutions (IFIs) due to Islamic banking's unique features that includes the prohibition of riba, gharar, maysir and other requirements that its activities must be in compliance with Shariah. Research on audit expectations gap in Shariah audit practices has received little attention by researchers. Three objectives are set in this study; these are: firstly to examine the perceptions of the internal auditors (Shariah auditors), regulators (BNM), Shariah committee, Shariah officers, external auditors and depositors concerning the Shariah audit practices in the Islamic banks in Malaysia. Secondly, the study determines the existence of expectations-performance gap between internal Shariah auditors, regulators (BNM), Shariah committee, Shariah officers, external auditors and depositors concerning the Shariah audit practices in the Islamic banks in Malaysia. Thirdly, the study analyse identity factors that affect the expectation gap on performance of Shariah audit. The study uses Porter’s (1993) framework on audit expectation-performance gap which classify the gap into reasonableness gap and performance gap. Mixed methods approached were used which involves interviews, questionnaires survey and analyzing factors that significantly related to expectation gap on performance in Shariah audit. The study found that a reasonableness gap exists in Shariah audit practices on framework, scope, independence, competency, processes, reporting, responsibility and Shariah auditor’s performance. Reasonableness gap in Shariah audit is the gap between what practitioners and stakeholders expects on the practices of Shariah audit and what it can reasonably be expected to accomplish. Based on the findings, there is also an existence of performance gap in Shariah audit practices which results in ‘deficient standards’ and ‘deficient performance’. The ‘performance gap’ in Shariah audit practices due to poor standards and deficient performance needs to be addressed to boost the performance of Shariah auditors. This study also found that performance gap due to ‘deficient standard’ as a result of inadequate legal and professional standards on the roles and responsibilities of Shariah auditors. This study further examine the factors that significantly affect the expectation gap on performance in Shariah audit. Based on the findings, factors such as competency, scope and independence significantly influence the Shariah auditor’s performance in the Shariah audit practices. Thus, there is a need to strengthen the competency, scope and independence of the Shariah audit to ensure greater effectiveness of the goals of Shariah compliance in Islamic Banks. The research provides new insights into the structure, practices and, more importantly, it rational and comprehensive approach towards narrowing the gap. As a consequences, good Shariah audit practice that meet the expectations of stakeholders will reduce the criticism an different expectations on the Shariah audit practices in the Islamic banks.